EFEK ANTIHIPERGLIKEMIA DARI EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus L.) YANG DIINDUKSI SUKROSA - Manurung, Sondang; Barung, Elisabeth; Bodhi, Widhi (PHARMACON, 2012)
This study aims to determine the effects of pericarp extracts of mangosteen antihiperglikemia in wistar strain male mice induced sucrose and compare its effectiveness with glibenclamide. The method used is a laboratory experiment using a Completely Randomized Design. Subjects in the form of 15 male white rats tail with weight ranging from 100g-210g are divided into 3 groups of each group as much as 5 tails. The treatment begins with administration of sucrose solution is adjusted to the weight of each rat. On the second day evening, the test animals fasted for twelve hours, and the third day in the morning followed by blood glucose level measured sucrose solution, after thirty minutes of administration of sucrose solution was measured blood glucose level, the first group were given distilled water, the second group were given mangosteen rind extract 20%, The third group was given glibenclamide and 0.3030 mg/g weight had made suspension in 1% CMC solution is then measured blood sugar test animals one, two, three, and four hours. Data were analyzed with spss ver.17, the real difference between treatments was tested by one way ANOVA. The results of statistical analysis gave a significant difference p-value=0.00 (p <0.05) in which the extract can suppress the KBM 20% increase in KGD in mice and provide similar effectiveness with glibenclamide. Key Word : Garcinia mangostana L., Rattus norvegicus L., Sucrose, CMC